Registration of Three Germplasm Lines of Cotton Derived from Gossypium barbadense L. Accession GB713 with Resistance to the Reniform Nematode. Issue 2 (25th January 2013) - McCarty, J. C.; Jenkins, J. N.; Wubben, M. J.; Gutierrez, O. A.; Hayes, R. W.; Callahan, F. E.; Deng, D.
Abstract : Three upland cotton ( Gossypium hirsutum L.) germplasm lines, M713 Ren1 (Reg. No. GP‐958, PI 665928), M713 Ren2 (Reg. No. GP‐959, PI 665929), and M713 Ren5 (Reg. No. GP‐960, PI 665930) resistant to the reniform nematode, Rotylenchulus reniformis Linford and Oliveria were developed and jointly released by the USDA‐ARS and the Mississippi Agricultural and Forestry Experiment Station in 2012. The day‐neutral, reniform‐resistant germplasm lines originated from the photoperiodic G. barbadense L. accession GB713 and were selected using the tightly linked simple sequence repeat (SSR) markers GH 132, BNL 3279, and BNL 569. Egg production of the reniform nematode was suppressed to approximately 90% below that of the susceptible check, 'Deltapine 61' in greenhouse tests. The lines exhibit considerable differences for agronomic and fiber traits such as length, strength and micronaire, and with their high level of resistance they should be valuable to cotton breeding programs. The successful use of marker assisted selection for these specific SSR markers further validates their use in the selection of resistant plants in segregating generations.